Reflux and dental disorders in the pediatric population: A systematic review. (September 2020) - Lechien, Jerome R.; CALVO-HENRIQUEZ, Christian; Chiesa-Estomba, Carlos M.; Barillari, Maria Rosaria; Trozzi, Marilena; Meucci, Duino; Peer, Shazia; Ben Abdelouahed, Fairouz; Schindler, Antonio; Saussez, Sven
Abstract: Objectives: To investigate the role of laryngopharyngeal reflux (LPR) or gastroesophageal reflux disease (GERD) in the development of dental disorders in pediatric population. Methods: PubMed, Scopus Cochrane database were assessed for subject headings using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) recommendations. Relevant studies published between January 1990 and January 2020 describing the association between reflux and dental disorders in children were retrieved. Three authors reviewed the LPR diagnosis method; inclusion criteria and outcomes. The bias analysis was performed through the tools of the Oxford Centre for Evidence-Based Medicine evidence levels. Results: The electronic search identified 126 publications, of which 11 clinical studies and 2 basic science researches met our inclusion criteria. There is an important heterogeneity between studies about diagnostic method and clinical outcome evaluation. All studies based the reflux diagnosis on GERD criteria. No author considered hypopharyngeal nonacid reflux episodes through hypopharyngeal-esophageal intraluminal multichannel impedance pH monitoring (HEMII-pH). The results of studies support a higher prevalence of dental erosion in children with GERD compared with healthy individuals. Controversial findings were found about the potential association between reflux and caries, and the modification of both saliva composition and production in reflux children. Conclusion: The association between reflux and dental disorder is still uncertain. Future studies considering pharyngeal acid and nonacid reflux episodes through HEMII-pH are needed to confirm this hypothesis. The pepsin detection in saliva would be an additional way for detecting LPR in children with dental disorders.